Collateral weight loss in children living with adult bariatric surgery patients: A case control study. (2nd July 2014) - Hirsch, Annemarie G.; Wood, G. Craig; Bailey‐Davis, Lisa; Lent, Michelle R.; Gerhard, Glenn S.; Still, Christopher D.
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of adult bariatric surgery on the body mass index (BMI) of children living in the same household. Methods A retrospective case‐control study. Case dyads (n = 128) were composed of one adult who had bariatric surgery and one child at the same address. Control dyads (n = 384) were composed of an adult with obesity but no bariatric surgery and a child at the same address. Two‐sample t‐test was used to determine whether the differences between actual and expected BMI at follow‐up (post‐surgery) differed between children in the case and control dyads. Results Among boys who were overweight, boys who lived with a surgery patient had a lower than expected BMI post‐surgery, while boys who did not live with a surgery patient had a higher than expected BMI at follow‐up (P = 0.045). Differences between actual and expected BMIs of children were not significantly different between cases and controls in girls or in children in other weight classes. Conclusions Overweight boys who lived with an adult bariatric surgery patient had a lower than expected BMI after surgery as compared to controls. Future studies may be warranted to determine the mechanisms by which these children experience collateral weight loss.